Gender and Sexuality in early 19th-century Tunisia: a Decolonial Reading of Aḥmad b. al-Qāḍī al-Timbuktāwī’s naṣīḥa on the sub-Saharan diaspora - Itzea Goikolea-Amiano (Genre & Histoire)
This article examines the gender and sexuality politics in early nineteenth-century Tunisia, with particular reference to the healing rituals performed by the diasporic sub-Saharans and the attempts at disciplining them by Muslim religious scholars. It does so through an in-depth analysis of a 1808 naṣīḥa penned by the West African scholar Aḥmad b. al-Qāḍī al-Timbuktāwī, where the Tunisian rulers are urged to ban the religious practices of the sub-Saharan populations—mainly slaves—which are deemed un-Islamic. In addition to close-reading the naṣīḥa, I contextualise and compare it with other texts and literature to ‘unveil’ not only al-Timbuktāwī’s discourse but also the history of enslaved sub-Saharans and the larger social, cultural and political history of early nineteenth-century Tunisia. I argue that al-Timbuktāwī’s request to ban the rituals was religiously motivated, but it also aimed at preventing the leadership and sexual intimacy which the rituals allegedly promoted, and I investigate whether such gender and sexual practices were perceived as disrupting the domestic Tunisian social and sexual order (or not).